2021
DOI: 10.1152/ajpgi.00113.2021
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for assessment of intestinal permeability in clinical practice

Abstract: Objectives: Intestinal permeability is an important diagnostic marker, yet its determination by established tests, which measure the urinary excretion of orally administered tracer molecules, is time-consuming and can only be performed prospectively. Here, we aim to validate proposed surrogate biomarkers which allow measuring intestinal permeability more easily. Methods: In this cross-sectional study, we included two independent cohorts, comprising non-obese (Healthy cohort, n = 51) and obese individuals (Obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 33 publications
2
63
0
1
Order By: Relevance
“…Free intake of feed containing SRP increased the expression of the antibacterial peptide Reg3γ in the cecum, suggesting that the intestinal barrier function, especially the chemical barrier, was enhanced in the mice. Indeed, the blood LBP level, a major marker of intestinal barrier failure (25)(26)(27), was significantly decreased in the SRP group. This indicated that SRP intake suppressed the invasion of microbes from the intestine into the body.…”
Section: Discussionmentioning
confidence: 93%
“…Free intake of feed containing SRP increased the expression of the antibacterial peptide Reg3γ in the cecum, suggesting that the intestinal barrier function, especially the chemical barrier, was enhanced in the mice. Indeed, the blood LBP level, a major marker of intestinal barrier failure (25)(26)(27), was significantly decreased in the SRP group. This indicated that SRP intake suppressed the invasion of microbes from the intestine into the body.…”
Section: Discussionmentioning
confidence: 93%
“…Fecal zonulin and plasma LBP, two recently validated markers for intestinal permeability [32], were examined after consumption of PT, FO, and fish. Neither the fecal zonulin nor the plasma LBP were negatively affected by PT consumption or any of the other challenges.…”
Section: Gut Barrier Function and Gut Microbiomementioning
confidence: 99%
“…At the same time, they showed increased LBP and I-FABP levels indicating more bacterial translocation and 'leaky gut' [56]. Furthermore, increased intestinal permeability in non-obese males with OSA (as compared to non-OSA subjects) showed significant associations with inflammatory mediators (serum IL-1β) [53], and zonulin levels in OSA patients correlated positively with some metabolic, inflammation and hepatic parameters [6]. Interestingly, OSAS children showed increased severity of inflammation and gut barrier damage-related strains as compared to healthy population [57].…”
Section: Discussionmentioning
confidence: 91%
“…Intestinal permeability will be assessed as surrogate biomarkers, i.e., zonulin, calprotectin, LPB and I-FABP concentration in blood serum. It has been shown that biomarkers from blood samples were associated with the cumbersome established tests of intestinal permeability throughout different cohorts [53]. Of SCFAs butyric, propionic and acetic acids level will be measured.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation